Recovery of cobalt from primary and secondary materials - an overiew - Stopić, Srećko; Friedrich, Bernd (Vojnotehnički glasnik / Military Technical Courier, 2020)
Introduction/purpose: Cobalt is a strategic metal for industrial application. Cobalt recovery from oxidic ores such as laterite and sulphidic ores, and from secondary materials during acidic treatment and precipitation is a highly used strategy ensuring different products such as cobalt hydroxide, cobalt oxide, and finally metallic cobalt. Methods: Familiarity with cobalt behavior in hydrometallurgical processes such as dissolution at atmospheric and high pressure, precipitation, neutralization, filtration and hydrogen reduction is most important for cobalt recovery from ores and secondary materials. Pyrometallurgical methods such as roasting and flash smelting are applied for the treatment of sulphidic ores combined with solvent extraction and electrolysis in order to obtain cathodic cobalt. Results: Powders of nickel-cobalt hydroxide were obtained from ores using sulphuric acid under high pressure in an autoclave and after precipitation with MgO. Solvent extraction was used to separate cobalt from nickel. The final step of cobalt recovery from a solution is using electrolysis. Cobalt and cobalt compounds such as cobalt carbonate and cobalt hydroxide can be obtained from secondary materials in hydrometallurgical operations. Conclusion: Hydrometallurgical and pyrometallurgical processes are mostly applied for cobalt recovery from primary ores (oxidic and sulphidic compounds) and from secondary materials (cemented tungsten carbide, polycrystalline diamond blanks, and waste cathodic materials from lithium-ion batteries).